Effects of honey and sucrose on longevity and fecundity of apanteles metesae (nixon), a major parasitoid of the oil palm bagworm, metisa plana (Walker) - Salmah, M; Basri, M.W; Idris, A.B (Universiti Kebangsaan Malaysia, 2012)
The effects of various concentrations of honey and sucrose on the longevity and fecundity of Apanteles metesae (Nixon), an endoparasitoid of oil palm bagworm, Metisa plana (Walker) (Lepidoptera: Psychidae) were studied in the laboratory. Our results showed that there were a significant difference (p<0.05) in the longevity of metesae fed on various concentrations of honey solutions. Longevity of A. metesae was significantly longer when fed on 50% honey than on pure honey. Nonetheless, longevity of metesae females fed on 50% honey was relatively longer than other honey concentrations. The parasitoid lived significantly longer when fed on 20% sucrose than when fed on 50% sucrose and distilled water. However, the parasitoid fed on 50% honey had a longevity that was statistically similar to 20% sucrose and 50% sucrose. Fecundity of metesae differed significantly (p<0.05) when fed on 50% honey, 20% sucrose and 50% sucrose. The highest and lowest fecundity was when the parasitoids fed on 20% sucrose and distilled water, respectively. Overall, the result showed that 20% sucrose was a more suitable diet for metesae females as compared with other diets.